The contribution of morbidity and unemployment for the reduced labor market participation of individuals with neurofibromatosis 1 in Finland - Kallionpää Roope A.; Johansson Edvard; Böckerman Petri; Peltonen Juha; Peltonen Sirkku (SPRINGERNATURE, 2025)
Neurofibromatosis 1 (NF1) is a multisystem disorder associated with, for example, a high risk for cancer, a variety of behavioral and cognitive deficits, low educational attainment and decreased income. We now examined the labor market participation of individuals with NF1. We analyzed the numbers of days of work, unemployment, and sickness allowance among 742 Finnish individuals with NF1 aged 20-59 years using nationwide register data from Statistics Finland and the Social Insurance Institution of Finland. The individuals with NF1 were compared with a control cohort of 8716 individuals matched with age, sex, and the area of residence. Individuals with NF1 had a significantly lower number of working days per year than the controls (rate ratio [RR] 0.93, 95% CI 0.91-0.95). Unemployment (RR 1.79, 95% CI 1.58-2.02), and sickness absence (RR 1.44, 95% CI 1.25-1.67) were more frequent in the NF1 than in the control group. The causes of sickness allowances were highly concordant with the previously reported morbidity profile of NF1 including neoplasms, cardiovascular disease, mental and behavioral diseases, and neurological diseases. In conclusion, NF1 significantly interferes with labor market participation via both unemployment and morbidity. Unemployment seems to cause more days of not working than sickness absence.